Hostilidade: uma revisão de literatura no referencial teórico junguiano - Siqueira, Guilherme Tavares de (2008)
The aim of this study was to review the literature on hostility in the Jungian theoretical context. Medical research has linked hostility to psychosomatic illnesses, self-destructive behaviour and the increase in violence. The review of knowledge on this theme would enable the health professional to perform more consciously. The review of the literature was based mainly on journals linked to the International Association of Analytical Psychology (IAAP) database and classical Jungian authors. From the material examined we concluded that there is no conceptual precision on this theme. The terms hostility, anger, aggressiveness, hatred, rage and violence are confused with each other. Different researchers sometimes use the same term with different meanings. However, despite the lack of terminological precision, there is consensus in the understanding of these phenomena. Hostility is related to illnesses resulting from disturbances in the autonomic nervous system, to an increase in violence, to attacks on the environment and to a deficiency in the person s sense of humanity. Hostility in its constructive aspect is important for creativity, interaction with the environment, expansion of consciousness and consolidation of the ego. In its destructive aspect it can be related to dysfunctions that arise prematurely on the ego-Self axis. As a product of culture, hostility is also understood to be a result of the devaluation and repression of the body and affections, values which are traditionally associated with femininity and erotic dynamics. Finally we emphasize the importance of studying hostility both on an individual level and collectively